-3x+5=x-13

Simple and best practice solution for -3x+5=x-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3x+5=x-13 equation:


Simplifying
-3x + 5 = x + -13

Reorder the terms:
5 + -3x = x + -13

Reorder the terms:
5 + -3x = -13 + x

Solving
5 + -3x = -13 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
5 + -3x + -1x = -13 + x + -1x

Combine like terms: -3x + -1x = -4x
5 + -4x = -13 + x + -1x

Combine like terms: x + -1x = 0
5 + -4x = -13 + 0
5 + -4x = -13

Add '-5' to each side of the equation.
5 + -5 + -4x = -13 + -5

Combine like terms: 5 + -5 = 0
0 + -4x = -13 + -5
-4x = -13 + -5

Combine like terms: -13 + -5 = -18
-4x = -18

Divide each side by '-4'.
x = 4.5

Simplifying
x = 4.5

See similar equations:

| X-1+5x=2x | | X(x+4)=525 | | 56-n=48 | | 0.30(d-1000000)=202500 | | 11x^2-8=2x | | 4i*i= | | Tan(64)=7/x | | 3+(x-2)=8 | | 10*190+6.25*177.8+5= | | 13x-16x+18x=60-26x+11x | | 2x^3-10x^2+40x=8x | | x^5+9=26 | | 2x^2-10x+40x=8x | | 2-2x=-5-x | | 3x^2-x=140 | | log(x+3)=log(x-3)+1.5 | | 3x^2+4-7x=0 | | B+63=19 | | -4=p+12 | | ln(x+3)=ln(x-3)+1.5 | | 4tanx=10 | | 8b+3=b | | 16+11h=9h | | 8x+26=4x+2 | | 7y-8=4y+31 | | (7x-68)=(-3+110) | | 6x+26=8x+12 | | 3y+-1=7 | | (3x-10)=(3x-2) | | 3x^2+y^2=4 | | M^2+8+16=0 | | 3y+2ln(x)=4ln(y+7) |

Equations solver categories